2019
DOI: 10.1109/access.2019.2927821
|View full text |Cite
|
Sign up to set email alerts
|

Smart Grid Simulation Including Communication Network: A Hardware in the Loop Approach

Abstract: Smart grids are complex electrical systems made up of power devices and communication systems that interact with each other, both locally through measures and generally through the exchange of information on communication networks. In this article, the simulation of a smart grid including the emulation of the communication network behavior together with the physical hardware devices is proposed using hardware-in-the-loop methodology. The original aspect of the technique is related to the fact that the models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…The HIL system developed in this study simulates the PVS with integration times of 10 µs, this timing, although turning out to be longer compared to the studies developed in commercial platforms, is similar to the results obtained in research reported in the literature; [32] obtains simulation periods between 1.1 and 19.9 ms, [43] reports periods of 20 µs, the platform developed by [46] presents periods of 5 µs, in the study by [44] results for this 10 µs variable are reported, [47] reports periods between 200 ns and 2 µs, in [42] a period of 1 ms is used and finally [40,41] report periods of 50 µs. On the other hand, if the response of the PVSE presented in Figure 22 is analyzed as a first order system, it would have a time constant of approximately 990 microseconds, which means that with the integration time of the PVS around 99 values are calculated for the output for each time constant, allowing to emulate a continuous signal.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The HIL system developed in this study simulates the PVS with integration times of 10 µs, this timing, although turning out to be longer compared to the studies developed in commercial platforms, is similar to the results obtained in research reported in the literature; [32] obtains simulation periods between 1.1 and 19.9 ms, [43] reports periods of 20 µs, the platform developed by [46] presents periods of 5 µs, in the study by [44] results for this 10 µs variable are reported, [47] reports periods between 200 ns and 2 µs, in [42] a period of 1 ms is used and finally [40,41] report periods of 50 µs. On the other hand, if the response of the PVSE presented in Figure 22 is analyzed as a first order system, it would have a time constant of approximately 990 microseconds, which means that with the integration time of the PVS around 99 values are calculated for the output for each time constant, allowing to emulate a continuous signal.…”
Section: Discussionsupporting
confidence: 77%
“…Ref. [46] uses an arrangement with cRIO, FPGAs and a processor to simulate a MG that includes a PVS, achieving simulation steps of around 5 µs. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The end-user premises enabled by HAN mainly implements AMI and demand response. For coordinating smart meter for its monitoring purposes, HAN deploys various wireless technologies like Wi-Fi (IEEE 802.11) and ZigBee (IEEE 802.15.4) [73]. Wired solutions may include the use of Ethernet and PLC.…”
Section: Smart Grid -Data Communication Systems Scenariomentioning
confidence: 99%
“…Due to this characteristic, FPGAs have been employed to perform cosimulation in Real-Time Simulators. A co-simulation can be defined as the division of a complex mathematical model to be simulated synchronously in different hardwares [6]. Realtime simulators are any machine capable of solving the model equations at the same time-step of the real-world system being simulated [7].…”
Section: Introductionmentioning
confidence: 99%